Pediatric Infectious Sacroiliitis: Characterization and Differentiation from Noninfectious Etiologies. Issue 7 (July 2019) - Vardi, Yoav; Levy, Itzhak; Ashkenazi-Hoffnung, Liat; Sherman, Gilad; Berger, Itay; Rom, Eran; Chodick, Gabriel; Landau, Daniel; Scheuerman, Oded
Abstract : Background: Pediatric sacroiliitis (SI) is an uncommon entity of infectious or inflammatory etiology. Recent data regarding pediatric SI are scarce. The study objective was to describe and compare the clinical features of pediatric infectious and noninfectious SI. Methods: We reviewed files of children ⩽18 years of age, admitted with SI in 2004–2017. Patients were grouped by etiology, infectious versus noninfectious. Clinical and laboratory indices, imaging, treatment protocols and outcome were compared. Results: Study population included 40 patients with infectious SI (range: 3–192 months, median age: 15 months, 45% female) and 13 patients with noninfectious SI (range: 30–216 months, median age: 168 months, 62% females). Duration of symptoms before admission averaged 5.9 ± 7.5 days in the infectious group and 54.2 ± 96 days in the noninfectious group ( P = 0.003). Symptoms observed solely in the infectious group included refusal to stand (n = 27, 77%); walk or crawl (n = 24, 65%); irritability (n = 20, 50%) and recent constipation event (n = 8, 20%). No significant differences in laboratory results were found. Infectious SI patients had uneventful medical history, rapid response to antibiotics and a higher rate of complete resolution of symptoms without recurrences. Conclusions: An acute unilateral presentation in young patients ⩽2 years of age, without chronic medical conditions, suggests an infectious etiology of SI anticipated to completely resolve with antibiotic treatment, not necessitating further workup for noninfectious etiologies.